SWOT Analysis of Bukit Jaddhih for Halal Tourism Village Destination in Bangkalan Regency - Dahruji , Dahruji; Mashudi, Mashudi; Arisandi , Bustomi (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
Bangkalan district is the closest district to the city of Surabaya than the cities on the island of Madura. This is an extraordinary potential of the economic sector, especially in the halal tourism sector. There are several tourist destinations that can be conceptualized in Bangkalan district, one of which is Jaddhih Hill Tourism which is located in Jaddhih village, Socah district, Bangkalan district. This destination is a tourist destination that explores the nature that exists in the village. This destination has not conceptually been conceptualized as a halal tourist destination, but considering that this is a 100% Muslim population, it certainly has its own potential to become a halal destination. With the SWOT analysis method, this research tries to analyze in terms of strengths, weaknesses, opportunities and challenges to be conceptualized as a halal tourist destination. The results of the calculations from IFAS and EFAS that have been carried out show the score value, namely Strengths of 3.13, Weaknesses of 2.24, Opportunities Factors of 3.31, Challenges Factors (Threats) of 2 ,33. So it can be concluded that the Bukit Jaddhih Tourism Object is very possible to be used as a Halal tourism village destination by approaching office holders both at the village level and at the government level. The challenges and weaknesses that need to be addressed are the availability of facilities to the location, security and public transportation that does not yet exist to the location as well as several matters relating to the development of these destinations